2004
DOI: 10.1242/jcs.01182
|View full text |Cite
|
Sign up to set email alerts
|

Localization and regulation of SR-BI in membrane rafts of HepG2 cells

Abstract: The scavenger receptor class B, type I (SR-BI) mediates cholesteryl esters (CE) selective uptake from low density lipoprotein (LDL) and high-density lipoprotein (HDL) particles. In a number of tissues expressing caveolin, SR-BI is localized in caveolae. We show using detergent-free sucrose gradients that SR-BI is found in membrane rafts devoid of caveolin-1 in the human hepatoma HepG2 cell. Perturbation of the structure of HepG2 cell membrane rafts with cholesterol oxidase or sphingomyelinase decreased LDL-CE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 73 publications
6
48
0
Order By: Relevance
“…6), which is closely associated with lipid rafts on plasma membranes (51-53). SR-BI can mediate the selective uptake of cholesteryl esters from both LDL and HDL particles, but these processes are affected differently by the integrity of lipid rafts on hepatocyte membranes (51). This effect might explain why there is a reduction of HDL-cholesterol and an induction of non-HDL-cholesterol (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6), which is closely associated with lipid rafts on plasma membranes (51-53). SR-BI can mediate the selective uptake of cholesteryl esters from both LDL and HDL particles, but these processes are affected differently by the integrity of lipid rafts on hepatocyte membranes (51). This effect might explain why there is a reduction of HDL-cholesterol and an induction of non-HDL-cholesterol (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HDL is internalized by a number of different cell types in an SR-BI-dependent manner (29,(32)(33)(34)(35)(36). This has led to an alternative model for selective CE uptake, in which HDL particles undergo lipid transfer during SR-BI-dependent internalization, sorting, and resecretion (32,33).…”
mentioning
confidence: 99%
“…[38][39][40] In addition, HepG2 cells have been shown to express high levels of HDL receptors that mediate selective uptake of cholesteryl esters (SR-BI) or holoparticle endocytosis (mitochondrial β chain of ATP synthase/P2Y13). 41,42 In the present study, the two Gd-labeled HDL nanoparticles were found to have different uptake properties. The uptake of Gd-chol-HDL was faster and more efficient.…”
Section: Discussionmentioning
confidence: 53%